MANAJEMEN KELAS PADA PENERAPAN KURIKULUM MERDEKA BELAJAR DI SEKOLAH DASAR - Berliani, Teti; Wahyuni, Rina; Nugroho, Piter Joko; Febriyanti, Lilik (Equity In Education Journal, 2024)
The Merdeka Belajar Curriculum (KMB) is an educational innovation that provides flexibility for teachers and students to develop a more independent and creative learning process. This study aims to analyze classroom management in implementing ETC at SDN 5 Bukit Tunggal Palangka Raya. The approach used in this research is qualitative, with data sources consisting of the principal and 4 teachers. Data were collected through observation, in-depth interviews, and documentation, which were then analyzed using thematic analysis techniques. Data validation used data triangulation and member check. The results showed that: (1) effective classroom management in the implementation of ETC involves the active role of teachers in creating an inclusive and dynamic learning environment; (2) teachers have flexibility in time management, learning methods, and assessment, which allows adaptation to individual student needs and potential; and (3) challenges faced by teachers are related to readiness in implementing ETC and the need for continuous training. Good classroom management is the key to success in implementing ETC, with full support from the school and adequate training for teachers.